A lifelong journey of lead in soil profiles at an abandoned e-waste recycling site: Past, present, and future. (1st March 2023) - Li, Yiren; Wang, Yanni; Liu, Jian; Gustave, Williamson; Zeng, Lingzao; Xu, Jianming; Liu, Xingmei
Abstract: Heavy metal pollutants resulting from human activities consistently move from the topsoil to the subsoil profiles under the influence of rainfall leaching. This study intends to predict the long-term transport of heavy metals at an abandoned e-waste recycling site with respect to historical pollution activities, land use, and metal pollutant dynamics. Our results showed that the site was seriously contaminated with heavy metals (Cd, Cu, Pb, and Zn) in the soil profiles. More specifically, Cu and Zn accumulated primarily in the upper layers of the soil profile owing to their weak mobility, while significant migration of Cd and Pb was observed in the deeper soil layers. Furthermore, to clarify the fate of Pb in soil profiles, Pb isotopes and the Hydrus model were used to trace the sources of Pb contamination and predict its long-term distribution. The Pb isotope results suggest that past e-waste recycling activities significantly contributed to the heavy metal concentration in the soil profiles; however, other anthropogenic sources such as vehicle exhaust had smaller impacts. Moreover, our model findings predicted that within the next 30 years, 60% of Pb contaminants will be concentrated in the surface soil. Together these results provide a theoretical foundation and scientific basis for evaluating, controlling, and remediating abandoned e-waste recycling sites. Graphical abstract: Image 1 Highlights: Significant migration of Cd and Pb was observed in the deep soil layers. E-waste recycling activities contributed greatly to the Pb accumulation by Pb isotopes. The long-term transport of metals was predicted based on the historical pollution activity. Contamination remains concentrated in the topsoil in 2050 by model prediction.